KOMPETENSI PENDIDIK DALAM AL-QUR’AN DAN RELEVANSINYA TERHADAP KOMPETENSI GURU MENURUT PERATURAN PEMERINTAH NOMOR. 74 TAHUN 2008 - Musyahadah, Arsyis; Al-Hamat, Anung; Mujahidin, Endin (Tawazun: Jurnal Pendidikan Islam, 2019)
Secularism and hedonism are now increasingly heavily attacking Islamic education. Contamination of Islamic education by Western culture can lead to skepticism and increasingly distanced students from their Lord. Teachers as educators are the determining factors of success of any educational endeavor.This study examines the concept of educators based on al-Qur’an and hadith and understanding of salaf ulama so that it can replace secular conventional education theories as well as adjust to the competence of teachers contained in PP RI. 78 Year 2008. The results of this study are first, the competence of educators through the study of interpretation Q.S ar-Rahman verses 1-5, Q.S al-Mudatsir verses 1-7 and Q.S al-’Alaq verses 1-5, among them are; Competence of noble character, spiritual competence, competence of science, competence of Islamization of science and science, professional competence, and social competence. Secondly, although teacher competence in Government Regulation and educator’s competence in al-Qur’an has relevance overall, but there are interesting concepts offered by the Qur’an that are not found in the Government Regulations on teacher competence. Among them are: spiritual competence and competence of Islamization of science and science. Keywords : Competence, Educator, Al-Qur’an